Potentiometric determination of coextraction constants of potassium salts in ion-selective electrodes utilizing a nitrobenzene liquid membrane phase - Silvester, Debbie; Grygolowicz-Pawlak, Ewa; Bakker, Eric (Elsevier BV, 2010)
A theoretical treatment of potentiometric data is applied to calculate coextraction constants (KIA) for three potassium salts from water into a liquid nitrobenzene phase. The experiment involves treating nitrobenzene as a membrane and contacting it with two aqueous solutions of different ion activities. In the presence of either a cation or anion exchanger, the ratio of activities of ions in the two aqueous phases gives rise to a potential difference across the membrane that depends upon the nature and charge of the counter ion of the ion-exchanger in excess. Here, the cation exchanger was chosen to be potassium tetrakis(4-chlorophenyl)borate (KTpClPB) and the anion exchanger was tetradodecylammonium chloride (TDDACl). TDDACl was incrementally added to the nitrobenzene phase containing a fixed concentration of KTpClPB, and the corresponding emf was recorded as a function of concentration of TDDACl. The membrane changes from one with cation exchanger properties (excess KTpClPB) to one with anion exchanger properties (excess TDDACl). The potential difference and shape of the titration curve can be predicted by theory based on the phase boundary potential model. Log(KIA) values calculated for KCl, KNO3 and KClO4 in nitrobenzene were found as: -10.53 (±0.09), -8.16 (±0.05) and -5.63 (±0.03) respectively, in accordance with the Hofmeister series of lipophilicity, and similar to those observed in PVC membranes containing other plasticizers. The method presented here offers the advantage over other methods to calculate KIA, in that it is relatively experimentally simple without compromising the accuracy of the calculated coextraction constants. The ability to titrate directly into the liquid membrane phase affords a higher precision compared to the preparation of a series of PVC/plasticizer membranes with different compositions.